Optimal Design of V-Shaped Fin Heat Sink for Active Antenna Unit of 5G Base Station - Chi-Cong Nguyen; Minh-Dinh Bui; Ngoc-Kien Nguyen; Van-Tinh Nguyen (Institute for Research and Community Services, Institut Teknologi Bandung, 2022)
The active antenna unit (AAU) is one of the main parts of the 5G base station, which has a large size and a high density of chipsets, and operates at a significantly high temperature. This systematic study presents an optimal design for the heat sink of an AAU with a V-shaped fin arrangement. First, a simulation of the heat dissipation was conducted on two designs of the heat sink – in-line and V-shaped fins – which was validated by experimental results. The result shows that the heat sink with V-shaped fins performed better compared to conventional models such as heat sinks with in-line fins. Secondly, computational fluid dynamics (CFD) and the Lagrange interpolation method were applied to find out an optimal set of design parameters for the heat sink. It is worth noting that the optimal parameters of the orientation angle and fin spacing considerably affected the heat sink’s performance.